1994
DOI: 10.1155/mbd.1995.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cisplatin and its Analogues on the Permeabilityof Human Erythrocyte Membrane

Abstract: The biomembrane is postulated as the initial target when Platinum(II) complexes attack cells. In this work, a spin-labeling ESR technique has been used to study the effects of cis-DCDP, cis-DBDP, cis-DIDP, trans-DCDP, and cis-DADP on the permeability of human erythrocyte membrane. We monitored the reduction processes of the ESR signal of a nitroxide spin label, (TEMPO), which leaks out through the membrane and is reduced by the external ascorbate. Our results indicate that cisplatin and its analogues can enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Overall literature data highlight that cisplatin interacts with lipid bilayers but its effect are complex and dependent on a variety of extrinsic factors, including pH and chloride concentration, as well as, membrane composition and other unknown factors (Mann et al, 1990; Lu et al, 1995a; Liang and Huang, 2002; Jensen and Nerdal, 2008). In fact, the importance of the physical state of membranes for the mechanisms of cisplatin and other platinum(II) complexes interaction remains to be determined.…”
Section: Cisplatin-membrane Interactionsmentioning
confidence: 99%
“…Overall literature data highlight that cisplatin interacts with lipid bilayers but its effect are complex and dependent on a variety of extrinsic factors, including pH and chloride concentration, as well as, membrane composition and other unknown factors (Mann et al, 1990; Lu et al, 1995a; Liang and Huang, 2002; Jensen and Nerdal, 2008). In fact, the importance of the physical state of membranes for the mechanisms of cisplatin and other platinum(II) complexes interaction remains to be determined.…”
Section: Cisplatin-membrane Interactionsmentioning
confidence: 99%
“…The biomembrane is postulated as the initial target when platinum (II) complexes attack cells. 33 Meanwhile platinum nanoparticles are a superoxide dismutase/catalase mimetic, 7 and convert hydrogen molecules to active hydrogen (atomic hydrogen). 10 In accordance with these studies, Pt/PVP-colloid or HW increased erythrocyte transformability and fluidity even in the presence of AAPH (Figs.…”
Section: Blood Fluidity and Erythrocyte Transforming Property Assessementioning
confidence: 99%
“…In the latter case, the cationic species may not be favored for interactions at this interface due to the hydrophobic characteristics created by height mismatch between lipids. Previous studies have reported that platinum complexes, including cisplatin and AqCis, were able to increase the permeability of erythrocyte membranes 38 and planar model membranes of hen's egg yolk (mostly composed of phospholipids of PC and PE), where the latter was attributed to the formation of small holes. 39 Our results suggest that indeed the permeability of the membrane is increased without major alterations of the lipid phase properties.…”
Section: Effects Of Cisplatin and Aqcis On Fluid And Gel Phasementioning
confidence: 99%